Pengunaan Arduino Uno Untuk Pengukuran Suhu, Ph dan Do Air Kolam Ikan Bawal Menggunakan Logika Fuzzy - Kridho Cokro Bagaskoro (JURIKOM (Jurnal Riset Komputer), 2019)
In paw fish cultivation, fish growth conditions will be optimal if the pH is in the range 7 - 8 for its own temperature is in the range 25 - 30 0C and for (Dissolved Oxygen) has a minimum concentration of oxygen dissolved (DO)> 4 pmm. Unstable conditions of temperature, pH and Dissolved Oxygen can cause water degradation, even in breeding of pomfret can cause fish to die. Therefore, it is necessary to do a periodic check on the pond to maintain the stability of temperature, pH and DO. To maintain the temperature stability of the pond water using LMH35 as a temperature sensor, then to maintain the pH stability of the water using the Electrode Eutech Instrument pH Meter Kit as pH sensor and while to check the minimum concentration of oxygen using Gravity sensor: Analog Dissolved Oxygen Sensor. The output of temperature, pH and DO water measurements in the process using fuzzy logic is displayed on the LCD screen and on the monitor in graphical form making it easier for the pomfret to monitor the condition of the fish pond water.